2021
DOI: 10.1088/1748-605x/ac15b1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting acute myeloid leukemia cells by CD33 receptor-specific MoS2-based nanoconjugates

Abstract: Acute myeloid leukemia (AML) is a highly aggressive type of cancer caused by the uncontrolled proliferation of undifferentiated myeloblasts, affecting the bone marrow and blood. Systemic chemotherapy is considered the primary treatment strategy; unfortunately, healthy cells are also affected to a large extent, leading to severe side effects of this treatment. Targeted drug therapies are becoming increasingly popular in modern medicine, as they bypass normal tissues and cells. Two-dimensional MoS2-based nanomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 96 publications
1
7
0
Order By: Relevance
“…These results are consistent with our previous findings that M75 antibody conjugated nanoplatforms are preferentially transported to organelles after 24 h of incubation . Nevertheless, in the case of the MoO x -M75 conjugates, we observed a relatively lower number of cells exhibiting lipoprotein aggregates compared with MoS 2 - or graphene oxide-based M75 conjugates. , An example of such structures can be seen in (ii) in Figure d, marked by orange color. The corresponding Raman spectra are shown in Figure S15.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent with our previous findings that M75 antibody conjugated nanoplatforms are preferentially transported to organelles after 24 h of incubation . Nevertheless, in the case of the MoO x -M75 conjugates, we observed a relatively lower number of cells exhibiting lipoprotein aggregates compared with MoS 2 - or graphene oxide-based M75 conjugates. , An example of such structures can be seen in (ii) in Figure d, marked by orange color. The corresponding Raman spectra are shown in Figure S15.…”
Section: Resultssupporting
confidence: 92%
“…Prior to cluster analysis, Principal Component Analysis (PCA) can be performed to reduce the dimensionality and lower the hyperspectral data noise. In our previous studies, we successfully visualized MoS 2 - , and GO-based , nanoflakes inside cellular matter using this method. The conjugates were localized in lysosome-rich cellular regions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute myeloid leukemia (AML) is the commonest leukemia that affects both adults and pediatrics. It is a haematological neoplasm that is characterized by uncontrolled proliferation and differentiation of hematopoietic precursor cells, which results in increased number of immature myeloblasts in the bone marrow (BM) and the peripheral blood (BP) of the patients [ 1 , 2 ]. In 2021, the American Cancer Society reported that AML was the second most commonly diagnosed leukemia and it was the leading cause of leukemia-related death in the United States [ 3 ].…”
Section: Introductionmentioning
confidence: 99%